A Connecticut Yankee in King Arthur's court - Twain, Mark, 1835-1910.; Hyman, Trina Schart (New York : W. Morrow, 1988)
Nineteenth-century mechanic Hank Morgan suffers a blow to the head and wakes up in King Arthur's Court where he tries to introduce modern technology and political ideas to the inhabitants.
Wilson's Fiction.
Wilson's Junior High School.
Wilson's Senior High School.
6.6
6.6
3-6.
Keywords: Arthur, -- King -- Juvenile fiction; Arthur, -- King -- Fiction; Arthur, -- King -- Fiction; Arthurian romances -- Adaptations; Knights and knighthood -- Fiction; Time travel -- Fiction; Americans -- Great Britain -- Fiction; Arthurian romances -- Adaptations; Historical fiction; Knights and knighthood -- Fiction; Time travel -- Fiction; Fantastic fiction